The performance of internet-only banks: Evidence from the U.S. in 2009-2018 - Shen, Shiming (2019)
This paper examines the financial performance of the Internet-only bank, and investigate whether the Internet-only bank can outperform the traditional bank. The analysis is based on the banks in the US from 2009 to 2018, and is measured by the fixed effects model. Overall, the empirical suggests that Internet-only banks tend to underperform traditional banks on profitability. Besides, there is no reduction in overhead costs due to the lack of physical branches. However, this paper further discusses the scale economies and experience economies between two different business models, examining whether technology can internalize additional scale effects or more experience effects. The results find that technology based scale and experience effects favour pure-play Internet banks, which means the technology skills indeed improve the performance.